2015
DOI: 10.1007/s00521-015-2039-0
|View full text |Cite
|
Sign up to set email alerts
|

An adaptive local linear optimized radial basis functional neural network model for financial time series prediction

Abstract: For financial time series, the generation of error bars on the point of prediction is important in order to estimate the corresponding risk. In recent years, optimization techniques-driven artificial intelligence has been used to make time series approaches more systematic and improve forecasting performance. This paper presents a local linear radial basis functional neural network (LLRBFNN) model for classifying finance data from Yahoo Inc. The LLRBFNN model is learned by using the hybrid technique of backpro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Neurons are topological networks in view of biological study and cerebrum reaction mechanism, simulating the step of nerve collide. e ends of a great deal of dendrites accept surface semaphore and convey them to neurons for processing and mixing together and last convey nerves to other neurons or effectors cross over axons [23][24][25][26][27][28]. e topological construction of neurons is shown in Figure 3.…”
Section: Bp Neural Networkmentioning
confidence: 99%
“…Neurons are topological networks in view of biological study and cerebrum reaction mechanism, simulating the step of nerve collide. e ends of a great deal of dendrites accept surface semaphore and convey them to neurons for processing and mixing together and last convey nerves to other neurons or effectors cross over axons [23][24][25][26][27][28]. e topological construction of neurons is shown in Figure 3.…”
Section: Bp Neural Networkmentioning
confidence: 99%
“…Neural Network (LLRBFNN) model to perform some prediction studies over financial time series [55]. The system has been successful enough on predictions and shown better performances than some other alternative systems reported in the study.…”
Section:  Patra Et Al Employed An Adaptive Local Linear (Optimized)mentioning
confidence: 94%
“…It was reported that the related system is successful enough in the prediction of EEG data [10]. A model of adaptive local linear (optimized) radial basis functional neural network (LLRBFNN) was employed by Patra et al to predict some financial time series [55]. It was reported in that study that LLRBFNN can perform predictions successfully enough and performs better than some other alternative systems that have been considered.…”
Section: A Brief Review Of the Literaturementioning
confidence: 99%